SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITIES OF Ni(II) AND Cu(II) COMPLEXES WITH SCHIFF BASE DERIVED FROM 2-ACETYL-5-METHYLFURAN GLYOXIME HYDRAZONE - Aliyu, H. N.; Adamu, H. (FUDMA JOURNAL OF SCIENCES, 2022)
A hydrazone Schiff base has been synthesized by the interaction of ethanolic solution of antiglyoxime hydrazine with 2-acetyl-5-methylfuran, to obtain the corresponding Schiff base L. The complexes of Ni(II) and Cu(II) of the Schiff base were synthesized and studied. The Schiff base and its metal(II) complexes characterized based on solubility, percentage yield, elemental analysis, melting/decomposition temperatures, infra- red spectral (FT-IR), conductivity measurement, magnetic susceptibility and water of crystallisation. The synthesized Schiff base and the complexes are coloured and stable at room temperature. Based on the results the prepared Schiff base and synthesized complexes are relatively soluble in most organic solvents but insoluble in distilled water. The melting point temperature of the ligand was 118oC while the decomposition temperature for metal complexes were 308 and 300oC respectively. The molar magnetic susceptibility of the complexes were 3.55 and 2.10 x 10-3 erg.G-2mol-1. The molar conductance values of 2.17 and 2.43ohm-1cm2mol-1 indicating non electrolytic nature of the complexes. The spectral data of the Schiff base showed band of 1584cm-1, revealing the formation of the azomethine. A bands of 791cm-1 indicate the metal nitrogen bond. The elemental analysis determination of the complexes and the Schiff base showed the metal ligand ratio of 1:2 (M:2L). The antibacterial and antifungal activities of the Schiff base and the metal(II) complexes were evaluated using disc diffusion method. The antibacterial assay was carried out on three pathogenic bacteria, Staphylococcus aureus, Staphylococcus epidermidis and Streptococcus pneumonia and two fungi viz: Candida utilis and Saccharomyces cerevisiae. All the Schiff base